Sarcoidosis Illuminations on Living During COVID-19: Patient Experiences of Diagnosis, Management, and Survival Before and During the Pandemic *. (March 2022) - Saketkoo, Lesley Ann; Jensen, Kelly; Nikoletou, Dimitra; Newton, Jacqui J.; Rivera, Frank J.; Howie, Mike; Reese, Rodney K.; Goodman, Melanie; Hart, Patricia B.; Bembry, Whitney; Russell, Adam; Lian, Isabelle; et al.
Background: Inspired by intense challenges encountered by patients and clinicians, we examined the experiences of living with sarcoidosis in three of the hardest impacted English-speaking cities during the early COVID-19 pandemic: London, New Orleans, and New York.Methods: A multi-disciplinary, multi-national research team including 6 patient leaders conducted qualitative investigations with analyses rooted in grounded theory. Recruitment occurred by self-referral through patient advocacy groups.Results: A total of 28 people living with sarcoidosis participated. The majority of patients had multi-system and severe sarcoidosis. Dominant themes were consistent across groups with differences expressed in spirituality and government and health systems. Racial, gender, and able-bodied inequity were voiced regarding healthcare access and intervention, societal interactions, and COVID-19 exposure and contraction. Agreement regarding extreme disruption in care and communication created concern for disability and survival. Concerns of COVID-19 exposure triggering new sarcoidosis cases or exacerbating established sarcoidosis were expressed. Pre-COVID-19 impediments in sarcoidosis healthcare delivery, medical knowledge, and societal burdens were intensified during the pandemic. Conversely, living with sarcoidosis cultivated personal and operational preparedness for navigating the practicalities and uncertainties of the pandemic. Optimism prevailed that knowledge of sarcoidosis, respiratory, and multi-organ diseases could provide pathways for COVID-19-related therapy and support; however, remorse was expressed regarding pandemic circumstances to draw long-awaited attention to multi-organ system and respiratory conditions.Conclusion: Participants expressed concepts warranting infrastructural and scientific attention. This framework reflects pre- and intra-pandemic voiced needs in sarcoidosis and may be an agent of sensitization and strategy for other serious health conditions. A global query into sarcoidosis will be undertaken.